USERS’ PERCEPTION OF PRIVATE PARK AND RIDE FACILITIES IN CAWANG AREA, JAKARTA, INDONESIA - Lubis, Harun al-Rasyid; Hasibuan, Bernard; Farda, Muhammad (Institut Teknologi Bandung, 2019)
Despite various measures implemented to manage road traffic, Jakarta City is still experiencing severe congestion. The concept, as well as the implementation of integrated urban transportation strategy, is gaining more attention in public discourse and policymaking. As bus and rail lines are being extended in the city, P&R facilities are expected to play an important role, as it can function as an interface between private vehicles and public transport. However, the development and use of P&R facilities have not been efficient until today. This paper reviews the P&R development in the Greater Jakarta area and conduct users? perception survey in private P&R sites at Cawang area. It was found that for the P&R to be attractive, the waiting time of public transport (BRT) connected to P&R facility should be short and predictable. Most P&R users expect that parking charges can be lowered and wish that public transport service and P&R facilities were available and accessible. The placement of advertisement and information system about the P&R services, providing a place to eat and drink, the presence of tower to monitor the P&R area and the availability of intermodal transfer facilities are also essential to encourage the potential user to use P&R facilities.